(untitled) (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
Soil damage due to excessive use of chemical fertilizers on potato vegetable crops is a real problem that must be solved. Through science learning with the Science Technology Society (STS) approach through the use of potato skins as organic fertilizer, it has helped reduce the use of chemical fertilizers. This study aims to foster scientific literacy in the area of awareness and concern for the environment. The research was conducted in class VII MTs Ma’arif Kejajar Wonosobo. This type of quantitative research with a true experimental approach pre-test-post-test control design. For data collection techniques with a questionnaire to see the attitude of awareness and concern for the environment. Data analysis was performed by t test. The results of the study showed that the t-test = 2.6> t table = 1.7. Science learning with the STS approach has a significant effect on scientific literacy in the area of awareness and concern for the environment.